A psychophysiological approach to fear appeals. Autonomic, subjective and behavioral responses to health promotion messages - Gonzalez Javier, Francisca; Gómez-Amor, jesús; Ordoñana, Juan R. (Anales de Psicología / Annals of Psychology, 2021)
A study was designed in order to analyze the effects of fear appeals on psychophysiological, subjective and behavioral responses on the target audience. Three messages on breast cancer, promoting regular mammography screening, elaborated in a similar way to those used by health promotion programs, were presented to ninety-eight women aged 49-50. Messages were of equal length, format and structure but varied in specific clues which distinguished their character (Threat, Surprise, and Standard/control). Psychophysiological reactions (heart rate and frequency of non- specific skin conductance responses) were recorded continuously during message exposure. Self-report measures and personality traits (STAI and EPQ-A) were obtained after viewing the stimulus. There were significant responses to the messages for all psychophysiological measures. The pattern of psychophysiological response, independent of the eliciting message, was significantly related to cancer preventive/detection behavior.